Active Transport to School and Children’s Body Weight: A Systematic Review - E. Masoumi, Houshmand (TeMA - Journal of Land Use, Mobility and Environment, 2017)
Because of decreasing physical activity of children, they are becoming more obese. Moreover, commuting to school has become more passive during the past decades. The objective was to update the previous systematic reviews by narrowing down the topic to body mass index of children (3-12 years) as a representative of body composition. Applying search terms such as active transport to school, body mass index, childhood obesity, and so on in four online databases: PubMed, ScienceDirect, WorldCat, and Google Scholar. Peer-reviewed English journal papers published between 2005 and 2015 presenting empirical quantitative studies were eligible studies to be reviewed. 310 journal papers were screened, 27 of which were reviewed by studying the full text. The final 13 papers were limited to those that focused only on active commuting to school and body mass index of children and adolescents. Out of 13 final studies, 3 found conclusive associations, three indicate partial associations in subgroups or societal or geographical limitations, and seven show no correlations. The existing literature are still inconsistent, so this study suggests conducting surveys with larger samples on less-studied contexts and applying more complex statistical methods for adjusting some of the variables. It is also argued that this topic can be culturally and contextually specific.